Nontraumatic Massive Spontaneous Hemothorax with Concomitant Warfarin Use. (12th May 2013) - Doğan, Nurettin Özgür; Pamukçu Günaydın, Gül; Tekin, Mustafa; Çevik, Yunsur
Abstract : Hemorrhagic complications due to warfarin use are frequently seen in emergency departments. However, nontraumatic massive hemothorax is an unexpected complication. We report a 59-year-old woman with warfarin overdose, who had massive hemothorax in right lung without any history of trauma. Her main complaint was significant dyspnea, which has gradually increased in three days. On her physical examination, she was tachypneic and had decreased lung sounds on her right hemithorax. She took warfarin regularly for aortic and mitral valve replacement for 18 years. Her INR level was 12.9 (0.8–1.2). Computed tomography of thorax revealed massive hemothorax with mediastinal shift. Fresh frozen plasma infusion was started immediately. Tube thoracostomy was performed for reexpansion of right lung and 2000 cc blood was drained in 5 minutes. Although hemorrhagic complications can be expected in warfarin therapy, thoracic hemorrhage related to warfarin therapy is relatively rare (3% of all hemorrhagic complications due to warfarin therapy). To our knowledge, massive hemothorax due to warfarin use is an extremely rare condition.